Evaluation of Dairy Cows Farm Management and Health in Several Regencies in East Java Province - Khasanah, Himmatul; Syaifudin, Faisal; Widianingrum, Desy Cahya (Jurnal Veteriner, 2024)
The demand for cow milk in Indonesia increases every year, but optimal production is not met. This study aimed to assess dairy cattle production management and health in East Java Province to construct improvement strategies and increase milk production. The research method was conducted through interviews with 63 dairy farmers from Sidoarjo, Mojoketo, Malang, Pasuruan, Probolinggo, Jember, and Banyuwangi regencies. This study indicates that 81% of farmers joined to livestock groups and sold fresh milk products to cooperatives or KUD (Koperasi Unit Desa). The average livestock ownership is 6.7 heads, with an average number of lactating cows of 4.5. The average price of milk sold to cooperatives or KUD was 5810 IDR/L and if it sold independently the price was 9769 IDR/L. Breeders provide forage feed as much as 34.67 kg/head/day and concentrate as much as 4.8 kg/head/day. The forage and concentrate feeding frequencies were 2.7 and 1 times a day. As many as 44% of farmers did not experience any problems or obstacles in the cultivation process carried out. A total of 66% faced obstacles that were dominated by feed factors (19.05%) and disease (17.46%). Diseases that infect (besides mastitis) are bloat (29%), hypocalsemia (18%), and diarrhea (7%). As an effort to prevent and increase production, farmers carry out preventive actions through the application of good farming practices (40%), maintaining the cleanliness of housing and livestock (24%), not making any effort (18%), applying feed management (10%), giving supplements and feed additives (8%). In conclusion, dairy farming management in East Java Province needs to be improved, and good husbandry practices need to be carried out by all farmers to increase cow’s milk production.